Cardiac Imaging Modalities in the Diagnosis of Coronary Artery Disease - Sun, Zhonghua (OMICS Publishing group, 2013)
Coronary artery disease is the leading cause of death in advanced countries. Early detection and diagnosis of coronary artery disease plays an important role in the identification of disease severity and prediction of disease outcome, consequently improving patient management. Diagnosis and management of coronary artery disease is increasingly dependent on less-invasive imaging modalities, including coronary CT angiography, cardiac magnetic resonance imaging, cardiac radionuclide imaging such as SPECT and PET modalities. Rapid developments of these imaging modalities have significantly improved the diagnostic performance of each imaging technique with high diagnostic accuracy achieved in both diagnostic and prognostic value in coronary artery disease. This editorial provides an overview of the diagnostic applications of a variety of less-invasive imaging modalities in the diagnosis of coronary artery disease. This special issue of “Arteriosclerotic Vascular Disease: Part II” in the journal of Clinical and Experimental Cardiology will give particular attention to contributions focusing on the clinical applications of these imaging modalities in the arteriosclerotic vascular disease, in particular, coronary artery disease.